Afganistan (Chast' 1) . Afganistan (Chast' 1) . Afghanistan (Part 1) . Афганистан (Часть 1) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. A concert, devoted the memory of the war in Afghanistan. Featured in the program: Gorbachev, Mikhail Sergeevich (Politician); Grachev, Pavel Sergeevich (Defense Minister of the Russian Federation) Концерт, посвященный памяти о войне в Афганистане. В программе участвуют: Горбачев, Михаил Сергеевич (Политик); Грачев, Павел Сергеевич (Министр обороны Российской Федерации)